Characterization of radioiodine therapy failures in Graves’ disease - Sabri, O.; Zimny, M.; Schreckenberger, M.; Reinartz, P.; Nowak, B.; Ostwald, E.; Schäfer, W.; Block, S.; Setam, K.; Büll, U. (Nuklearmedizin - NuclearMedicine, 2001)
Aim of this study was a characterization of radioiodine therapy (RIT) failures in Graves’ disease without simultaneous Carbimazole. Method: 226 patients with a confirmed diagnosis of Graves’ disease received 686.8 ± 376.4 MBq of iodine-131 orally for thyroid ablation. Target dose was 250 Gy. All patients were followed up for 6 months. Therapy failures were compared with successes regarding possible influencing variables initial thyroid volume, thyroid function, immune activity (TRAb), 1-131 uptake, effective half-life, absorbed energy dose, age and gender. Results: 212 of 226 patients (93.8%) were treated successfully, 14 (6.2%) showed a hyperthyroidism relapse within 6 months which required a second radioiodine therapy. A success rate of 92.5% (62/67) could also be achieved with 67 patients who were hyperthyroid at the time of RIT. Compared to the therapy successes, the 14 failures achieved significantly lower absorbed doses (223.8 ±76.6 Gyvs. 285.2 ±82.1 Gy, ρ <0.005), but with no significant differences regarding age, thyroid volume, function or TRAb (all ρ >0.2). Of the 14 failures, η = 8 reached an absorbed dose <200 Gy and η = 1 a dose <250 Gy, although 5 of the failures reached an absorbed dose of >250 Gy. Stepwise logistic regression revealed only absorbed energy dose as a variable significantly influencing therapy success (p <0.005), but no influence of initial thyroid volume, function, TRAb value, age (all ρ >0.2) or gender (p = 0.13). Two-tailed Fisher’s exact test showed no significant influence of gender on success rates (failures/successes: male 1 /36, female 13/176, ρ = 0.48). Conclusions: Except for the absorbed energy dose, no other significant variable influencing the outcome of radioiodine therapy in Graves’ disease without simultaneous Carbimazole could be found. It should be noted, though, that 5 therapy failures (2.2%) reached an absorbed energy dose of >250 Gy.
Keywords: Graves’ disease; radioiodine therapy; thyrostatic medication; energy dose; thyroid volume; thyroid function